Development, evaluation and application of reperfused liver infarction in rats as a practical model for studying ischemic diseases and screening new drugs. (26th April 2010) - Wang, Huaijun; Wu, Xia; Chen, Feng; Jin, Lixin; Li, Junjie; Feng, Yuanbo; DeKeyzer, Frederik; Yu, Jie; Jiang, Yansheng; Verbruggen, Alfons; Marchal, Guy; Ni, Yicheng
Appropriate animal models of human diseases often lead to important discoveries in biomedical sciences. An animal model of reperfused liver infarction (RLI) in rats has been introduced and applied originally as an easier substitute of brain and heart infarction for developing necrosis-avid contrast agents (NACAs) to enhance the sensitivity and specificity of magnetic resonance imaging (MRI) in diagnosis of ischemic cardiovascular diseases such as acute myocardial infarction and stroke and in the assessment of certain tissue destroying therapies. The ever-advancing MRI technology has enabled comprehensive in vivo non-invasive characterisation of this model to gain further insight into its morphological and functional specifications and to implicate its broader utilities for preclinical developments of new diagnostics and therapeutics. The in vivo MRI outcomes have been further validated by postmortem microangiography and histology. The present mini review article aims to highlight a number of relevant aspects about the RLI model in rats and to facilitate those interested academic or industrial researchers to apply this model in their own experimental studies.